(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Breast cancer mortality rate is fifth among all cancer and increasing day by day due to modern lifestyles. Its molecular subtype is classified as per their significant receptor expression, such as estrogen receptor (ER), progesterone receptor (PR) & human epidermal growth receptor 2 (Her2). Triple-negative breast cancer (TNBC) is an aggressive subgroup among breast cancer subtypes and clinically challenging to treat due to loss of all three receptor (ER/PR/Her2) expression. Treatment modalities of TNBC include surgery, chemotherapy, radiotherapy and immunotherapy. Postoperative radiation therapy (RT) improves locoregional control and overall survival in TNBC patients. The powerful ionizing radiation (IR) response to RT is contributed by the inherent radiosensitivity of the tumor, which is influenced by genes associated with the cell cycle, DNA damage repair, apoptosis, etc. This review article narrates the role of biomarkers obtained through data mining and manual curation of published literature to predict radioresistance in patients receiving radiotherapy. Further, the role of natural radiosensitizers in overcoming radioresistance for effectively managing TNBC is also discussed.